Sex Differences in the Association Between Cortisol Concentrations and Laboratory Pain Responses in Healthy Children - Allen, Laura B. (2009)
BACKGROUND: Research in adult populations has highlighted sex differences in cortisol concentrations and laboratory pain responses, with men exhibiting higher cortisol concentrations and reduced pain responses compared with women. Yet, less is known about the relationship of cortisol concentrations to pain in children. OBJECTIVE: This study examined associations between sex, cortisol, and pain responses to laboratory pain tasks in children. METHODS: Salivary cortisol samples from subjects aged 8 to 18 years were obtained at baseline after entering the laboratory (SCb), after the completion of all pain tasks (SC1), and at the end of the session (SC2), 20 minutes later. Blood cortisol samples were also taken after completion of the pain tasks (BC1) and at the end of the session (BC2), 20 minutes later. Subjects completed 3 counterbalanced laboratory pain tasks: pressure, heat, and cold pressor tasks. Pain measures included pain tolerance, and self-reported pain intensity and unpleasantness for all 3 tasks. RESULTS: The study included 235 healthy children and adolescents (119 boys, 116 girls; mean age, 12.7 years; range, 8–18 years; 109 [46.4%] were in early puberty; 94 [40.0%] white). Salivary and blood cortisol levels were highly correlated with each other. Salivary cortisol levels for the total sample and for boys and girls declined significantly from SCb to SC1 (P < 0.01), although there were no significant changes from SC1 to SC2. No significant sex differences in salivary or blood cortisol levels were evident at any assessment point. Separate examination of the cortisol–laboratory pain response relationships by sex (controlling for age and time of day) suggested different sex-specific patterns. Higher cortisol levels were associated with lower pain reactivity (ie, increased pressure tolerance) among boys compared with girls at SC1, SC2, and BC1 (SC1: r = 0.338, P = 0.003; SC2: r = 0.271, P = 0.020; and BC1: r = 0.261, P = 0.026). However, higher cortisol levels were related to higher pain response (ie, increased cold intensity [BC2: r = 0.229, P = 0.048] and unpleasantness [BC1: r = 0.237, P = 0.041]) in girls compared with boys. CONCLUSIONS: These findings suggest important sex differences in cortisol–pain relationships in children and adolescents. Cortisol levels were positively associated with increased pain tolerance in boys and increased pain sensitivity in girls.